0410 Insufficient Sleep Among Healthcare Professionals. (27th May 2020) - Jenkins, D; Peprah, R; Donley, T; Sexias, A; Khosrof, A; Jean-Louis, G
Abstract: Introduction: Insufficient sleep (IS) is a common problem among healthcare professionals, especially those who are shift workers. Evidence has shown that sleeping less than eight hours can lead to sleep debt. Sleep debt can have a negative impact on the mental, emotional and cognitive well-being of health care providers. In addition to sleep debt, having long shift hours reduces the opportunity for sleep because there is less time to recuperate. Methods: We analyzed data gathered from healthcare workers (n=4, 093) from the 2017 and 2018 National Health Interview Survey (NHIS), a nationally representative study of the US civilian non-institutionalized population. Sleep was categorized as short (≤6 hrs), normal/healthy (7-8 hrs), and long (≥9 hrs) sleep. Using STATA 15.0 for Windows, we report weighted frequencies and Chi square tests. Alpha of 0.05 was used for all significance levels. Results: Of the sample, 18% were male and 82% were female. The mean age was 50.7±17.5. The majority of the sample was White (77%), 12% were Black and 9% were of other minority". The proportion of women who reported short sleep (31%) and normal (45%) were significantly higher than men (p<0.000). Healthcare workers under 30 had the highest proportions of short sleep compared to any other age groups (p<0.000). Lower numbers were associated with long sleep among those who worked directly with patients compared to workers who did not (p<0.000). Healthy sleep was significantly associated with not having trouble falling asleep, staying asleep, not taking sleep medications, and feeling rested 7 or more times in the past week (p<0.000). Conclusion: Our study explores sleep patterns among healthcare professionals. Previous studies have shown that this population is more susceptible to insufficient sleep which leads to sleep debt. We found that the current data suggest that this association may have changed for healthcare professionals today. Support: This study was supported by funding from the NIH: R01MD007716, R01HL142066, K01HL135452, and K07AG052685.